Da’wah about Politics Carried Out by Islamic Groups in the Cyber Islamic Environment - Kurniawan, Dadang; Ghulam, Zainil (Dakwah, 2025)
This study discusses the use of social media by Nahdlatul Ulama (NU) through the NU Online platform as a medium for political da'wah during the 2024 General Election in Indonesia. This article uses the Cyber ​​Islamic Environment (CIE) theoretical framework by Gary R. Bunt and the participatory culture theory by Henry Jenkins to examine how social media is used to convey Islamic-based political ideas. This study found that NU Online utilizes social media to promote the values ​​of moderation, inclusivity, and Islam in politics through informative and educational content. In addition, the participatory culture on social media allows the Nahdliyyin community to play an active role in creating, disseminating, and discussing political content. The results of the study show that social media is not only a communication tool, but also an arena for the exchange of political and religious ideas. These findings emphasize the importance of digital media as a discursive space in shaping political and religious identities in the digital era.